A ZnO resistor for DC lightning arrester and its preparation method

By adding specific dopants to the DC zinc oxide resistor sheet, such as Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, Ga-Hf-Al2O3 and SiO2 loaded with cerium oxide, and through the doping of gallium and hafnium, the aging performance problem of the DC zinc oxide resistor sheet during polarity conversion is solved, achieving higher anti-aging performance and longer service life.

CN118530016BActive Publication Date: 2025-03-07XIAN TIANGONG ELECTRIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410716013.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2025-03-07
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

The aging performance of DC zinc oxide resistors during polarity conversion is poor, resulting in a shortened service life. Traditional AC lightning arresters also have aging problems in DC applications.

Method used

Using ZnO resistor sheet containing Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, Ga-Hf-Al2O3 and doped SiO2 loaded with cerium oxide, the cerium oxide is uniformly dispersed by the loading of silicon dioxide, increasing the stability of the resistor sheet, and improving the current transmission capability and structural stability through the doping of gallium and hafnium.

Benefits of technology

The anti-aging performance of zinc oxide resistor sheet is significantly improved, especially under polarity conversion conditions, which extends the service life of the resistor sheet and reduces power consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004875591660000111
    Figure BDA0004875591660000111
Patent Text Reader

Abstract

The present application relates to the field of lightning arresters, and specifically discloses a ZnO resistor for DC lightning arresters and a preparation method thereof. The resistor is made of the following raw materials: Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, Ga-Hf-Al2O3, doped SiO2 loaded with cerium oxide, SiO2, silver glass powder, Al(NO3)3﹒9H2O, and the rest is ZnO; the preparation method comprises the following steps: the raw materials are ball-milled and calcined for the first time and then ball-milled to obtain a calcined material; zinc oxide is dispersed in water, the calcined material, Al(NO3)3, a dispersant, a defoaming agent and an adhesive are added, and the mixture is stirred to obtain a slurry; spray granulation, pressing and molding, debinding, pre-firing, sintering, spraying glass glue, glazing, heat treatment, grinding, cleaning, drying, and then spraying aluminum electrodes to obtain a resistor for lightning arresters; the present application has the characteristics of further improving the anti-aging performance of zinc oxide resistors under polarity conversion conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lightning arresters, and more specifically, to a ZnO resistor sheet for a DC lightning arrester and a preparation method thereof. Background Art

[0002] As the requirements for power system protection and grid levels gradually increase, the role of lightning arresters in power system protection devices is becoming increasingly important. Metal oxide lightning arresters, as a new type of lightning arrester, have been widely used in power grid systems since their emergence in the 1970s. Their core structure is a zinc oxide (ZnO) resistor. Multiple zinc oxide resistors are tightly connected to form a zinc oxide valve column. The two ends of the valve column are connected to springs and electrodes. The springs play the role of compressing the valve column. After sealing, they are encapsulated with a composite insulating jacket and a composite porcelain jacket.

[0003] With the advantages of large transmission capacity, long transmission distances, and the ability to connect to asynchronous power systems, DC transmission line arresters are widely used in my country's power transmission systems. DC transmission line arresters are urgently needed protective components for DC transmission systems. DC zinc oxide resistors, made of varistor ceramic materials, are the core components of DC transmission line arresters. Due to the characteristics and operating mode of DC power, the aging effect of DC power on equipment and materials is more significant and severe than that of AC power. Therefore, the aging effect of DC zinc oxide resistors is more severe than that of AC resistors. If traditional AC arresters are used in DC applications, they will quickly experience increasing power consumption due to aging, ultimately leading to thermal breakdown.

[0004] In DC systems, arresters withstand long-term operating voltages without changing polarity. However, when a DC arrester undergoes a polarity reversal, the zinc oxide resistor is subjected to high voltage and current shocks for a short period of time. This causes changes in the resistor's internal microstructure, accelerates the resistor's aging process, and shortens its service life. Current research on DC zinc oxide resistors has not examined their aging performance during polarity reversals. Improving the aging resistance of DC zinc oxide resistors, especially during polarity reversals, is crucial for improving their performance. Summary of the Invention

[0005] In order to further improve the anti-aging performance of zinc oxide resistors under polarity conversion conditions, the present application provides a ZnO resistor for a DC lightning arrester and a preparation method thereof.

[0006] In a first aspect, the present application provides a ZnO resistor for a DC lightning arrester, adopting the following technical solution: a ZnO resistor for a DC lightning arrester, made from the following raw materials in weight percentage: 2-5% Bi2O3, 1.5-4.5% Sb2O3, 0.8-2.3% NiO, 0.3-2.8% Co3O4, 0.2-2.5% MnCO3, 0.5-1.5% Ga-Hf-Al2O3, 0.1-1.0% doped SiO2 loaded with cerium oxide, 0.1-0.5% SiO2, 0.03-0.5% silver glass powder, 0.01-0.05% Al(NO3)3﹒9H2O, and the rest ZnO.

[0007] By adopting the above technical solution, the silicon dioxide in the resistor of the present application uses a combination of doped silicon dioxide loaded with cerium oxide and undoped silicon dioxide. While the insulating properties of silicon dioxide are exerted to reduce the leakage current of the resistor during operation, some silicon dioxide is added after loading doped cerium oxide CeO2. Through the loading effect of silicon dioxide, cerium oxide CeO2 can be more evenly dispersed in the DC zinc oxide resistor, reducing its agglomeration phenomenon and increasing the stability of the resistor. In addition, the loading of metal elements increases the carrier concentration and improves its conductive properties. It may be that during subsequent processing, cerium oxide and silicon dioxide form a certain amount of cerium silicate, and cerium silicate forms a unique crystal structure with zinc oxide. It may also be that cerium oxide and zinc oxide form a stable crystal structure, or the addition of cerium oxide helps aluminum and zinc oxide form a solid solution. It was found that loading cerium oxide on silicon dioxide and adding it significantly improves the anti-aging properties of the resistor, especially the aging performance during polarity conversion.

[0008] In addition, the present application also adds aluminum oxide doped with gallium and hafnium. The addition of aluminum oxide can effectively improve the power consumption caused by the high voltage and high current impact performance of the resistor during polarity conversion, and improve the aging performance during polarity conversion. More importantly, the doping of gallium helps to form a solid solution with zinc oxide. The addition of aluminum oxide doped with gallium forms a solid solution with zinc oxide, thereby realizing the doping of the above-mentioned metal elements in the zinc oxide lattice, stabilizing the lattice structure, reducing defects, and improving its stability and aging resistance. The doping of hafnium metal elements, combined with the DC zinc oxide resistor, makes the resistor have better current transmission capability, and helps to enhance the structural stability of the resistor, and is more resistant to high voltage and current under polarity conversion conditions, reduces power consumption during polarity conversion, and improves the aging resistance of the resistor. Finally, the zinc oxide resistor prepared by the present application has better aging resistance, especially excellent aging resistance under polarity conversion conditions.

[0009] Optionally, Ga-Hf-Al2O3 is prepared by the following method:

[0010] Aluminum nitrate is dissolved in water, acetylacetone is added and mixed, and the mixture is heated to 35-45°C and kept warm for 20-30 minutes. Then, hydrated gallium nitrate and hafnium tetrachloride are added, followed by monoethanolamine solution and ammonia solution. After stirring, ethylene glycol is added, and the mixture is heated to 80-95°C, and then continued to be heated to 120-150°C and reacted for 2-3 hours. Then, the mixture is calcined at 450-500°C for 2-3 hours and cooled to room temperature to obtain Ga-Hf-Al2O3 doped with gallium and hafnium.

[0011] By adopting the above technical solution, in the present application, aluminum nitrate is first dissolved in water to obtain an aluminum-containing aqueous solution, and then a preliminary colloid is formed under the action of acetylacetone. The colloid is then heated to promote stability and formation. Gallium and hafnium elements are then introduced as dopants, and then their uniform distribution in the alumina sol-gel process is promoted under the action of monoethanolamine and ammonia water. Finally, heating is performed to remove moisture and organic matter, promote the formation of alumina crystals and the uniform distribution of doping elements, and prepare Ga-Hf-Al2O3 doped with gallium and hafnium.

[0012] Optionally, when preparing Ga-Hf-Al2O3, the raw materials are added according to the following weight parts: 60-70 parts of aluminum nitrate, 100-115 parts of water, 20-30 parts of acetylacetone, 30-40 parts of hydrated gallium nitrate, 30-40 parts of hafnium tetrachloride, 10-20 parts of monoethanolamine, 15-25 parts of ammonia solution, and 15-30 parts of ethylene glycol, and the mass concentration of the ammonia solution is 20-30%.

[0013] Optionally, the cerium oxide-loaded doped SiO2 is prepared by the following method:

[0014] The silicon dioxide is first immersed in a mixed solution of sodium chloride solution, lithium chloride solution and potassium nitrate solution and then dried to obtain porous silicon dioxide;

[0015] Porous silica is added to a mixture of hydroxyethyl cellulose and water, followed by a dispersant, cerium nitrate and ammonium bicarbonate, and the mixture is stirred. The mixture is then filtered, washed, dried, and calcined to obtain doped SiO2 loaded with cerium oxide.

[0016] By adopting the above technical solution, silicon dioxide is first dispersed in a mixed solution of sodium chloride, lithium chloride and potassium nitrate and immersed, and then dried to adjust the pore structure of the silicon dioxide, so as to obtain silicon dioxide with a pore structure of 8-10 nm. The silicon dioxide is then added to a mixed solution of hydroxyethyl cellulose and water, and then cerium nitrate and ammonium bicarbonate are added after adding a dispersant. The cerium nitrate and ammonium bicarbonate are co-precipitated to form a cerium oxide precursor loaded in the pore structure of carbon dioxide. Subsequently, the cerium oxide is calcined to form micro-nano-level cerium oxide in the pore structure, so as to realize the loading of cerium oxide on silicon dioxide. The addition of hydroxyethyl cellulose prevents the sedimentation of silicon dioxide, and the addition of the dispersant can inhibit the agglomeration of the cerium hydroxide precursor formed after the addition of cerium nitrate and ammonium bicarbonate, so as to obtain nano-cerium oxide with a size of 1-5 nm, thereby realizing the loading of cerium oxide in the pore size of silicon dioxide.

[0017] Optionally, when preparing doped SiO2 loaded with cerium oxide, the dispersant is sodium lauryl sulfate and sodium polymethacrylate in a mass ratio of 1:(1-2).

[0018] By adopting the above technical solution, the addition of sodium dodecyl sulfate increases the repulsive force of cerium hydroxide generated after the reaction of cerium nitrate and ammonium bicarbonate, reducing the agglomeration phenomenon, while the addition of sodium polymethacrylate prevents the agglomeration of the above particles through the steric hindrance effect, ultimately producing nano-cerium oxide with a smaller particle size, achieving loading in the pores of silica.

[0019] Optionally, when preparing doped SiO2 loaded with cerium oxide, after adding a dispersant, cerium nitrate and ammonium bicarbonate are added under plasma discharge treatment conditions, with a plasma treatment power of 1-2 KW and a gas pressure of 0.5-0.8 MPa.

[0020] By adopting the above technical solution, a dispersant is added to the mixed solution containing silicon dioxide and then treated under plasma discharge treatment conditions. The plasma treatment affects the pore structure of silicon dioxide, which is more conducive to the subsequent loading of cerium oxide.

[0021] Optionally, when preparing doped SiO2 loaded with cerium oxide, the mass ratio of the addition of sodium chloride solution, lithium chloride solution and potassium nitrate solution is 1:(1-1.5):(0.8-1.2), and the mass concentration of the sodium chloride solution is 25-35%, the mass concentration of the lithium chloride solution is 40-50%, and the mass concentration of the potassium nitrate is 20-30%, and the mixed solution is immersed in the silica;

[0022] The addition mass ratio of hydroxyethyl cellulose to water is 1:8-9, and the addition amount of hydroxyethyl cellulose is 0.5-1.5wt% of the porous silica, the addition amount of the dispersant is 1-3wt% of the mixed solution, and the addition mass ratio of porous silica, cerium nitrate and ammonium carbonate is 1:(0.2-0.3):(0.1-0.2).

[0023] Optionally, after adding cerium nitrate and ammonium bicarbonate, the calcination parameters are: first treating at 80-90° C. for 1-2 hours, and then calcining at 350-400° C. for 2-3 hours.

[0024] In a second aspect, the present application provides a method for preparing a ZnO resistor sheet for a DC lightning arrester, using the following technical solution:

[0025] A method for preparing a ZnO resistor for a DC lightning arrester comprises the following steps:

[0026] S1. Ball milling Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, SiO2, SiO2 doped with cerium oxide, Ga-Hf-Al2O3 and silver glass powder for the first time, calcining and then ball milling again to obtain a calcined material;

[0027] S2. Dispersing zinc oxide in water, then adding the calcined material prepared in step S1, dissolved Al(NO3)3, a dispersant, a defoaming agent and a dissolved binder, stirring and mixing to prepare a slurry;

[0028] S3, spraying the slurry into granules, then pressing and forming, removing binders, pre-firing, firing, spraying glass glue, glazing, heat treatment, grinding, and then cleaning and drying and spraying aluminum electrodes to obtain resistor sheets for lightning arresters.

[0029] By adopting the above technical solution, the resistor prepared by the method of the present application has excellent anti-aging performance, especially reducing power consumption under polarity conversion conditions and improving aging performance under polarity conversion conditions.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. In the resistor of the present application, part of the silicon dioxide is loaded with cerium oxide CeO2 and then added. Through the loading effect of silicon dioxide, the cerium oxide can be more evenly dispersed in the DC zinc oxide resistor, reducing its agglomeration phenomenon and increasing the stability of the resistor. In addition, the loading of metal elements increases the carrier concentration and improves its conductivity. It may be that during subsequent processing, cerium oxide and silicon dioxide form a certain amount of cerium silicate, and cerium silicate forms a unique crystal structure with zinc oxide. It may also be that cerium oxide and zinc oxide form a stable crystal structure, or the addition of cerium oxide helps aluminum and zinc oxide form a solid solution. It is found that loading cerium oxide on silicon dioxide and adding it significantly improves the aging resistance of the resistor, especially the aging performance during polarity conversion; 2. The invention also adds aluminum oxide doped with gallium and hafnium. The gallium doping helps to form a solid solution with zinc oxide. The addition of gallium-doped aluminum oxide forms a solid solution with zinc oxide, thereby realizing the doping of the above-mentioned metal elements in the zinc oxide lattice, stabilizing the lattice structure, reducing defects, and improving its stability and anti-aging performance. The doping of hafnium metal elements, combined with the DC zinc oxide resistor, makes the resistor have better current transmission capability and helps to enhance the structural stability of the resistor. It can better resist high voltage and current under polarity conversion conditions, reduces power consumption during polarity conversion, and improves the anti-aging performance of the resistor. Finally, the zinc oxide resistor prepared in this application has better anti-aging performance, especially excellent anti-aging performance under polarity conversion conditions. DETAILED DESCRIPTION

[0032] The present application is further described in detail below with reference to the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0033] In the following examples and preparation examples, the silicon dioxide used was mesoporous silicon dioxide from Qinghe Chaotai Metal Materials Co., Ltd., and its pore size was 2-3 nm.

[0034] The following preparation example is an example of the preparation of SiO2 doped with cerium oxide

[0035] Preparation Example 1

[0036] A method for preparing doped SiO2 loaded with cerium oxide comprises the following steps:

[0037] 1) First, the silicon dioxide is immersed in a mixed solution of sodium chloride solution, lithium chloride solution and potassium nitrate solution for 1.5 hours, and the mixed solution completely covers the silicon dioxide. The immersion temperature is 40° C., and then dried to obtain porous silicon dioxide;

[0038] The mass concentration of the sodium chloride solution is 30%, the mass concentration of the lithium chloride solution is 45%, and the mass concentration of the potassium nitrate solution is 25%, and the mass ratio of the sodium chloride solution, the lithium chloride solution and the potassium nitrate solution is 1:1.2:1;

[0039] 2) Based on 1 kg of porous silica treatment, the porous silica obtained in step 1) was added to a mixture of hydroxyethyl cellulose and water, and then a dispersant was directly added at room temperature, followed by cerium nitrate and ammonium bicarbonate. The mixture was stirred, filtered, washed, dried, and calcined. The specific calcination parameters were: treatment at 85° C. for 1.5 h, followed by calcination at 380° C. for 2.5 h to obtain doped SiO2 loaded with cerium oxide;

[0040] Among them, the dispersant is sodium lauryl sulfate and sodium polymethacrylate with a mass ratio of 1:1.5; the added mass ratio of hydroxyethyl cellulose and water is 1:8, the added mass ratio of porous silica, cerium nitrate and ammonium carbonate is 1:0.2:0.2, the added amount of dispersant is 2wt% of the mixed solution, and the added amount of hydroxyethyl cellulose is 1.0wt% of the porous silica.

[0041] Preparation Example 2

[0042] A method for preparing doped SiO2 loaded with cerium oxide comprises the following steps:

[0043] 1) First, the silicon dioxide is immersed in a mixed solution of sodium chloride solution, lithium chloride solution and potassium nitrate solution for 1 hour, and the mixed solution completely covers the silicon dioxide. The immersion temperature is 45° C., and then dried to obtain porous silicon dioxide;

[0044] The mass concentration of the sodium chloride solution is 25%, the mass concentration of the lithium chloride solution is 40%, and the mass concentration of the potassium nitrate solution is 20%, and the mass ratio of the sodium chloride solution, the lithium chloride solution and the potassium nitrate solution is 1:1:0.8;

[0045] 2) Based on 1 kg of porous silica treatment, the porous silica obtained in step 1) was added to a mixture of hydroxyethyl cellulose and water, and then a dispersant was directly added at room temperature, followed by cerium nitrate and ammonium bicarbonate. The mixture was stirred, filtered, washed, dried, and calcined. The specific calcination parameters were: treatment at 80° C. for 2 h, followed by calcination at 350° C. for 3 h, to obtain doped SiO2 loaded with cerium oxide;

[0046] Among them, the dispersant is sodium lauryl sulfate and sodium polymethacrylate in a mass ratio of 1:1; the added mass ratio of hydroxyethyl cellulose and water is 1:8, the added mass ratio of porous silica, cerium nitrate and ammonium carbonate is 1:0.2:0.1, the added amount of the dispersant is 1wt% of the mixed solution, and the added amount of hydroxyethyl cellulose is 0.5wt% of the porous silica.

[0047] Preparation Example 3

[0048] A method for preparing doped SiO2 loaded with cerium oxide comprises the following steps:

[0049] 1) First, the silicon dioxide is immersed in a mixed solution of sodium chloride solution, lithium chloride solution and potassium nitrate solution for 2 hours, and the mixed solution completely covers the silicon dioxide. The immersion temperature is 35° C., and then dried to obtain porous silicon dioxide;

[0050] The mass concentration of the sodium chloride solution is 35%, the mass concentration of the lithium chloride solution is 50%, and the mass concentration of the potassium nitrate is 30%, and the mass ratio of the sodium chloride solution, the lithium chloride solution and the potassium nitrate solution is 1:1.5:1.2;

[0051] 2) Based on 1 kg of porous silica treatment, the porous silica obtained in step 1) was added to a mixture of hydroxyethyl cellulose and water, and then a dispersant was directly added at room temperature, followed by cerium nitrate and ammonium bicarbonate. The mixture was stirred, filtered, washed, dried, and calcined. The specific calcination parameters were: treatment at 90° C. for 1 hour, followed by calcination at 400° C. for 2 hours to obtain doped SiO2 loaded with cerium oxide;

[0052] Among them, the dispersant is sodium lauryl sulfate and sodium polymethacrylate in a mass ratio of 1:2; the added mass ratio of hydroxyethyl cellulose and water is 1:8, the added mass ratio of porous silica, cerium nitrate and ammonium carbonate is 1:0.3:0.2, the added amount of the dispersant is 3wt% of the mixed solution, and the added amount of hydroxyethyl cellulose is 1.5wt% of the porous silica.

[0053] Preparation Example 4

[0054] A method for preparing doped SiO2 loaded with cerium oxide is carried out according to the method in Preparation Example 1, except that in step 2), plasma discharge treatment is also performed after adding the dispersant, the plasma treatment power is 1KW, the air pressure is 0.5MPa, and after treating for 30 minutes, cerium nitrate and ammonium bicarbonate are added for stirring treatment.

[0055] Preparation Example 5

[0056] A method for preparing doped SiO2 loaded with cerium oxide is carried out according to the method in Preparation Example 1, except that in step 2), plasma discharge treatment is also performed after adding the dispersant, the plasma treatment power is 2KW, the gas pressure is 0.8MPa, and after treating for 30 minutes, cerium nitrate and ammonium bicarbonate are added for stirring treatment.

[0057] Preparation Example 6

[0058] A method for preparing doped SiO2 loaded with cerium oxide is carried out according to the method in Preparation Example 1, except that no dispersant is added in step 2).

[0059] The following preparation example is the preparation example of Ga-Hf-Al2O3

[0060] Preparation Example 7

[0061] A method for preparing Ga-Hf-Al2O3 comprises the following steps:

[0062] 65g of aluminum nitrate was dissolved in 110g of water, 25g of acetylacetone was added and mixed, the mixture was heated to 40°C and kept warm for 25min, then 35g of gallium nitrate nonahydrate and 35g of hafnium tetrachloride were added, followed by 15g of monoethanolamine and 20g of 25% ammonia solution by mass, and 22g of ethylene glycol was added after stirring. The mixture was heated to 85°C, and then continued to be heated to 130°C and reacted for 2.5h. The mixture was then calcined at 480°C for 2.5h and cooled to room temperature to obtain Ga-Hf-Al2O3 doped with gallium and hafnium.

[0063] Preparation Example 8

[0064] A method for preparing Ga-Hf-Al2O3 comprises the following steps:

[0065] 60g of aluminum nitrate was dissolved in 100g of water, 20g of acetylacetone was added and mixed, the mixture was heated to 35°C and kept warm for 30min, then 30g of gallium nitrate nonahydrate and 30g of hafnium tetrachloride were added, followed by 10g of monoethanolamine and 15g of 20% ammonia solution by mass, and 15g of ethylene glycol was added after stirring. The mixture was heated to 80°C, and then continued to be heated to 120°C and reacted for 3h. The mixture was then calcined at 450°C for 3h and cooled to room temperature to obtain Ga-Hf-Al2O3 doped with gallium and hafnium.

[0066] Preparation Example 9

[0067] A method for preparing Ga-Hf-Al2O3 comprises the following steps:

[0068] 70g of aluminum nitrate was dissolved in 115g of water, 30g of acetylacetone was added and mixed, the mixture was heated to 45°C and kept warm for 20min, then 40g of gallium nitrate nonahydrate and 40g of hafnium tetrachloride were added, followed by 20g of monoethanolamine and 25g of a 30% ammonia solution by mass, and 30g of ethylene glycol was added after stirring. The mixture was heated to 95°C, and then continued to be heated to 150°C and reacted for 2h. The mixture was then calcined at 500°C for 2h and cooled to room temperature to obtain Ga-Hf-Al2O3 doped with gallium and hafnium.

[0069] Comparative Preparation Example 1

[0070] A method for preparing Hf-Al2O3 comprises the following steps:

[0071] Dissolve 65g of aluminum nitrate in 110g of water, add 25g of acetylacetone and mix, heat to 40°C and keep warm for 25 minutes, then add 35g of hafnium tetrachloride, then add 20g of 25% ammonia solution, stir and add 22g of ethylene glycol, heat to 85°C, then continue heating to 130°C and react for 2.5h, then calcine at 480°C for 2.5h, and cool to room temperature to obtain Hf-Al2O3 doped with hafnium.

[0072] Comparative Preparation Example 2

[0073] A method for preparing Ga-Al2O3 comprises the following steps:

[0074] Dissolve 65g of aluminum nitrate in 110g of water, add 25g of acetylacetone and mix, heat to 40℃ and keep warm for 25min, then add 35g of gallium nitrate nonahydrate, add 15g of monoethanolamine, stir and add 22g of ethylene glycol, heat to 85℃, then continue heating to 130℃ and react for 2.5h, then calcine at 480℃ for 2.5h, and cool to room temperature to obtain Ga-Al2O3 doped with gallium.

[0075] In the following examples, the dispersant used in the resistor preparation process is ammonium polyacrylate;

[0076] The defoamer used is a polyether defoamer, the brand is Zhonglianbond, model is B-299;

[0077] Polyvinyl alcohol is used as the adhesive.

[0078] Example 1

[0079] A method for preparing a ZnO resistor for a DC lightning arrester comprises the following steps:

[0080] S1. Ingredients: Prepare the raw materials according to the formula of mass percentage:

[0081] 3% Bi2O3, 2.5% Sb2O3, 1.5% NiO, 1.5% Co3O4, 1.5% MnCO3, 1.0% Ga-Hf-Al2O3, 0.5% cerium oxide-loaded doped SiO2, 0.3% SiO2, 0.1% silver glass powder, 0.03% Al(NO3)3﹒9H2O, and the remainder ZnO, wherein the cerium oxide-loaded doped SiO2 is the cerium oxide-loaded doped SiO2 prepared in Preparation Example 1, and the Ga-Hf-Al2O3 is the Ga-Hf-Al2O3 prepared in Preparation Example 7;

[0082] Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, SiO2, SiO2 doped with cerium oxide, Ga-Hf-Al2O3 and silver glass powder were initially ball-milled to less than 2 μm, then calcined at 800 °C for 1.5 h, and then ball-milled again to obtain a calcined material of 1.0 ± 0.2 μm;

[0083] S2. Disperse zinc oxide in water, then add the calcined material prepared in step S1, dissolved Al(NO3)3, dispersant, defoamer and dissolved binder, stir for 2 hours, mix to prepare a slurry, and control the solid content of the slurry to 65%;

[0084] S3, granulation: drying and granulating the slurry prepared in step S2 using a spray dryer to obtain granules with an average particle size of 100 μm;

[0085] Compression molding: 1.5% water was then added to the prepared granules in the form of a spray using a V-shaped water-containing mixer and mixed for 1.5 hours. The water-containing granules were then aged for 36 hours and then compression molded to obtain cylindrical embryos.

[0086] Debinding, pre-sintering, and firing: The pressed green body is placed in a mullite sagger and then subjected to debinding, pre-sintering, and firing in a pusher kiln to obtain ceramic sheets. The debinding temperature is 400°C, the pre-sintering temperature is 850°C, and the firing temperature is 1100°C. All three processes are carried out in separate zones in the pusher kiln.

[0087] Spraying glass adhesive: Carboxymethyl cellulose, glycerol, and water are mixed in a mass ratio of 1:0.7:2.5 to prepare an adhesive solution. Then, glass powder and the adhesive solution are stirred and evenly mixed in a mass ratio of 1:0.4 to obtain a glass slurry. The obtained glass slurry is then sprayed on the side of the ceramic piece.

[0088] Glazing and heat treatment: The ceramic sheet with glass slurry sprayed on the side was heat treated at 530℃ for 2.5h;

[0089] Grinding, cleaning and drying: then grinding, cleaning and drying;

[0090] Aluminum spraying electrode: Aluminum electrodes are sprayed on the upper and lower end surfaces of the ground ceramic sheet, and the full aluminum electrode is fully covered by the full electrode aluminum spraying equipment to obtain a resistor sheet for lightning arrester. Its structure includes a cylindrical zinc oxide varistor, glass glaze on the side of the resistor and aluminum electrodes on the upper and lower end surfaces of the varistor.

[0091] Example 2

[0092] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that: S1, ingredients: prepare the raw materials according to the formula of mass percentage:

[0093] 2% Bi2O3, 1.5% Sb2O3, 0.8% NiO, 0.3% Co3O4, 0.2% MnCO3, 0.5% Ga-Hf-Al2O3, 0.1% cerium oxide-loaded doped SiO2, 0.1% SiO2, 0.03% silver glass powder, 0.01% Al(NO3)3﹒9H2O, and the remainder ZnO, wherein the cerium oxide-loaded doped SiO2 is the cerium oxide-loaded doped SiO2 prepared in Preparation Example 2, and the Ga-Hf-Al2O3 is the Ga-Hf-Al2O3 prepared in Preparation Example 8;

[0094] Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, SiO2, SiO2 doped with cerium oxide, Ga-Hf-Al2O3 and silver glass powder were initially ball-milled to less than 2 μm, then calcined at 750 °C for 2 h and then ball-milled again to obtain a calcined material of 1.0 ± 0.2 μm.

[0095] In step S2, the solid content of the slurry is controlled at 60%;

[0096] In step S3, compression molding: 1% water is then added to the prepared granules in the form of a spray using a V-shaped water-containing mixer and mixed for 1 hour. The water-containing granules are then aged for 24 hours and then compression molded to obtain a cylindrical embryo body;

[0097] Debinding, pre-sintering, and firing: The pressed green body is placed in a mullite sagger and then subjected to debinding, pre-sintering, and firing in a pusher kiln to obtain ceramic sheets. The debinding temperature is 350°C, the pre-sintering temperature is 750°C, and the firing temperature is 1100°C. All three processes are carried out in separate zones in the pusher kiln.

[0098] Glazing and heat treatment: The ceramic piece with glass slurry sprayed on the side is heat treated at 450℃ for 3h.

[0099] Example 3

[0100] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that: S1, ingredients: prepare the raw materials according to the formula of mass percentage:

[0101] 5% Bi2O3, 4.5% Sb2O3, 2.3% NiO, 2.8% Co3O4, 2.5% MnCO3, 1.5% Ga-Hf-Al2O3, 1.0% cerium oxide-loaded doped SiO2, 0.5% SiO2, 0.5% silver glass powder, 0.05% Al(NO3)3﹒9H2O, and the remainder ZnO, wherein the cerium oxide-loaded doped SiO2 is the cerium oxide-loaded doped SiO2 prepared in Preparation Example 3, and the Ga-Hf-Al2O3 is the Ga-Hf-Al2O3 prepared in Preparation Example 9;

[0102] Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, SiO2, SiO2 doped with cerium oxide, Ga-Hf-Al2O3 and silver glass powder were initially ball-milled to less than 2 μm, then calcined at 850 °C for 1 h and then ball-milled again to obtain a calcined material of 1.0 ± 0.2 μm;

[0103] In step S2, the solid content of the slurry is controlled at 70%;

[0104] In step S3, compression molding: 2% water is then added to the prepared granules in the form of a spray using a V-shaped water-containing mixer and mixed for 2 hours. The water-containing granules are then aged for 48 hours and then compression molded to obtain a cylindrical embryo body;

[0105] Debinding, pre-sintering, and firing: The pressed green body is placed in a mullite sagger and then subjected to debinding, pre-sintering, and firing in a pusher kiln to obtain ceramic sheets. The debinding temperature is 450°C, the pre-sintering temperature is 900°C, and the firing temperature is 1100°C. All three processes are carried out in separate zones in the pusher kiln.

[0106] Glazing and heat treatment: The ceramic piece with glass slurry sprayed on the side is heat treated at 600℃ for 2h.

[0107] Examples 4-6

[0108] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that the cerium oxide-loaded doped SiO2 in step S1 is the cerium oxide-loaded doped SiO2 prepared in Preparation Examples 4-6.

[0109] Comparative Example 1

[0110] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that:

[0111] In step S1, the doped SiO2 loaded with cerium oxide is replaced with an equal amount of SiO2.

[0112] Comparative Example 2

[0113] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that:

[0114] In step S1, doped SiO2 loaded with cerium oxide is not added.

[0115] Comparative Example 3

[0116] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that the doped SiO2 loaded with cerium oxide in step S1 is replaced with SiO2 and cerium oxide CeO2. Specifically, the raw material formula in step S1 is as follows:

[0117] 3% Bi2O3, 2.5% Sb2O3, 1.5% NiO, 1.5% Co3O4, 1.5% MnCO3, 1.0% Ga-Hf-Al2O3, 0.65% SiO2, 0.15% CeO2, 0.1% silver glass powder, 0.03% Al(NO3)3﹒9H2O, and the remainder ZnO, wherein Ga-Hf-Al2O3 is the Ga-Hf-Al2O3 prepared in Preparation Example 7;

[0118] The addition of SiO2 during ball milling in step S1 is replaced by the addition of SiO2 and CeO2.

[0119] Comparative Example 4

[0120] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that:

[0121] The Ga-Hf-Al2O3 in step S1 is replaced by Al2O3 in equal amounts.

[0122] Comparative Example 5

[0123] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that an equal amount of Ga-Hf-Al2O3 in step S1 is replaced by Hf-Al2O3 prepared in Comparative Preparation Example 1.

[0124] Comparative Example 6

[0125] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method in Example 1, except that an equal amount of Ga-Hf-Al2O3 in step S1 is replaced by Ga-Al2O3 prepared in Comparative Preparation Example 2.

[0126] Comparative Example 7

[0127] A method for preparing a ZnO resistor for a DC lightning arrester is carried out according to the method of Example 1, except that: the Ga-Hf-Al2O3 in step S1 is replaced by Al2O3, HfO2, and Ga2O3. Specifically, in step S1, raw materials are prepared according to the following formula in mass percentage: 3% Bi2O3, 2.5% Sb2O3, 1.5% NiO, 1.5% Co3O4, 1.5% MnCO3, 0.5% Al2O3, 0.25% Ga2O3, 0.25% HfO2, 0.5% SiO2 doped with cerium oxide, 0.3% SiO2, 0.1% silver glass powder, 0.03% Al(NO3)3﹒9H2O, and the remainder is ZnO;

[0128] The addition of Ga-Hf-Al2O3 during ball milling in step S1 is replaced by the addition of Al2O3, HfO2 and Ga2O3.

[0129] Performance testing

[0130] The DC resistors prepared in the examples and comparative examples of the present application were subjected to unipolar DC aging and DC aging performance tests with polarity conversion, respectively. Specifically, the unipolar DC aging test method is as follows: accelerated DC aging is performed at 115°C for 1000 hours, during which the polarity of the applied voltage remains unchanged, and Kct is the ratio of the power consumption after 1000 hours of applied voltage to the initial power consumption; the DC aging test with polarity conversion is as follows: in combination with IEC60099-9, accelerated DC aging is performed at 115°C for 1000 hours, during which the polarity of the applied voltage needs to be changed 24 hours, 72 hours, 168 hours, and 360 hours after the voltage is applied, P0 is the power consumption measured 0.5 hours after the voltage is applied, and P9 is the power consumption measured after 1000 hours of applied voltage. The DC aging performance P9 / P0 under polarity conversion is calculated, and the test results are shown in Table 1 below:

[0131] Table 1:

[0132]

[0133] Referring to the test results in Table 1 above, it can be seen that the DC zinc oxide resistor prepared in the examples of the present application has excellent anti-aging performance, and it also has excellent anti-aging performance under polarity conversion, thereby reducing power loss under polarity conversion and increasing the service life of the zinc oxide resistor. Referring to the test results of Example 1 and Examples 4-5, when preparing doped SiO2 loaded with cerium oxide, when it is treated under plasma discharge conditions, the anti-aging performance of the final resistor can be further improved; combined with the test of Example 6, it can be seen that when preparing doped SiO2 loaded with cerium oxide, no dispersant was added, which may affect the control of the cerium oxide particle size, and ultimately affect the loading effect in porous silica, thereby affecting the aging performance of the final resistor.

[0134] Referring again to the test results of Example 1 and Comparative Examples 1 and 2, it can be seen that when no doped SiO2 loaded with cerium oxide is added in Comparative Example 2, the aging resistance of the zinc oxide resistor obtained is weak, especially the aging resistance under polarity conversion is significantly reduced. Referring again to Comparative Example 1, when the amount of silicon dioxide added to the raw material continues to increase, its aging resistance does not increase, and the residual pressure ratio and flow performance are reduced. Referring again to the test results of Comparative Example 3, when silicon dioxide and cerium oxide are added separately without loading, its aging resistance is improved compared to Comparative Example 2, but it is still relatively large, especially the aging resistance under polarity conversion is low;

[0135] Referring to the test results of Comparative Example 4, when gallium and hafnium elements are not added to the raw materials, the anti-aging performance during polarity conversion is poor, and when only gallium or hafnium elements are doped in the alumina in Comparative Examples 5 and 6, the anti-aging performance under polarity conversion is still poor. Combined with the test results of Comparative Example 7, when aluminum oxide, gallium oxide and hafnium oxide are added at the same time without doping, the anti-aging performance under polarity conversion is still weak.

[0136] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A ZnO resistor for DC lightning arrester, characterized in that: It is prepared from the following raw materials in weight percentage: 2-5% Bi2O3, 1.5-4.5% Sb2O3, 0.8-2.3% NiO, 0.3-2.8% Co3O4, 0.2-2.5% MnCO3, 0.5-1.5% Ga-Hf-Al2O3, 0.1-1.0% SiO2 doped with cerium oxide, 0.1-0.5% SiO2, 0.03-0.5% silver glass powder, 0.01-0.05% Al(NO3)3﹒9H2O, and the rest is ZnO; Ga-Hf-Al2O3 was prepared by the following method: Aluminum nitrate is dissolved in water, acetylacetone is added and mixed, and the mixture is heated to 35-45°C and kept warm for 20-30 minutes, and then hydrated gallium nitrate and hafnium tetrachloride are added, and then monoethanolamine solution and ammonia solution are added, and ethylene glycol is added after stirring, and the mixture is heated to 80-95°C, and then continued to be heated to 120-150°C and reacted for 2-3 hours, and then calcined at 450-500°C for 2-3 hours, and then cooled to room temperature to obtain Ga-Hf-Al2O3 doped with gallium and hafnium; The cerium oxide-loaded doped SiO2 is prepared by the following method: The silicon dioxide with a pore size of 2-3 nm is first immersed in a mixed solution of a sodium chloride solution, a lithium chloride solution and a potassium nitrate solution, and then dried to obtain porous silicon dioxide; Porous silica is added to a mixture of hydroxyethyl cellulose and water, and then a dispersant is added, followed by cerium nitrate and ammonium bicarbonate, and the mixture is stirred, filtered, washed, dried, and calcined to obtain doped SiO2 loaded with cerium oxide.

2. The ZnO resistor for DC lightning arrester according to claim 1, characterized in that: When preparing Ga-Hf-Al2O3, each raw material is added according to the following weight parts: 60-70 parts of aluminum nitrate, 100-115 parts of water, 20-30 parts of acetylacetone, 30-40 parts of hydrated gallium nitrate, 30-40 parts of hafnium tetrachloride, 10-20 parts of monoethanolamine, 15-25 parts of ammonia solution, 15-30 parts of ethylene glycol, the mass concentration of the ammonia solution is 20-30%.

3. The ZnO resistor for DC lightning arrester according to claim 1, characterized in that: When preparing doped SiO2 loaded with cerium oxide, the dispersant is sodium dodecyl sulfate and sodium polymethacrylate in a mass ratio of 1:(1-2).

4. The ZnO resistor for DC lightning arrester according to claim 1, characterized in that: When preparing doped SiO2 loaded with cerium oxide, after adding the dispersant, cerium nitrate and ammonium bicarbonate are added under plasma discharge treatment conditions. The plasma treatment power is 1-2KW and the gas pressure is 0.5-0.8MPa.

5. The ZnO resistor for DC lightning arrester according to claim 1, characterized in that: When preparing doped SiO2 loaded with cerium oxide, the mass ratio of sodium chloride solution, lithium chloride solution and potassium nitrate solution is 1: (1-1.5): (0.8-1.2), and the mass concentration of sodium chloride solution is 25-35%, the mass concentration of lithium chloride solution is 40-50%, and the mass concentration of potassium nitrate is 20-30%, and the mixed solution immerses the silica; The mass ratio of hydroxyethyl cellulose to water is 1:8-9, and the amount of hydroxyethyl cellulose added is 0.5-1.5wt% of the porous silica, the amount of dispersant added is 1-3wt% of the mixed solution, and the mass ratio of porous silica, cerium nitrate and ammonium carbonate added is 1: (0.2-0.3): (0.1-0.2).

6. The ZnO resistor for DC lightning arrester according to claim 1, characterized in that: After adding cerium nitrate and ammonium bicarbonate, the calcination parameters are: first treating at 80-90°C for 1-2h, and then calcining at 350-400°C for 2-3h.

7. A method for preparing a ZnO resistor for a DC lightning arrester according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Ball-milling Bi2O3, Sb2O3, NiO, Co3O4, MnCO3, SiO2, SiO2 doped with cerium oxide, Ga-Hf-Al2O3 and silver glass powder for the first time, then calcining and ball-milling again to obtain a calcined material; S2, dispersing zinc oxide in water, then adding the calcined material prepared in step S1, the dissolved Al(NO3)3, the dispersant, the defoamer and the dissolved binder, stirring and mixing to prepare a slurry; S3, spraying the slurry into granules, and then pressing and molding, removing binder, pre-burning, firing, spraying glass glue, glazing, heat treatment, grinding, and then cleaning and drying and spraying aluminum electrodes to obtain resistor sheets for lightning arresters.

Citation Information

Patent Citations

  • Ceramic having high voltage gradient, low residual voltage and low leakage current and preparation method thereof

    AU2020102274A4

  • High-performance direct-current zinc oxide varistor and preparation process thereof

    CN105427977A